Association of Body Mass Index With Risk Factor Optimization and Guideline-Directed Medical Therapy in US Veterans With Cardiovascular Disease. Issue 1 (January 2019) - Hira, Ravi S.; Kataruka, Akash; Akeroyd, Julia M.; Ramsey, David J.; Pokharel, Yashashwi; Gurm, Hitinder S.; Nasir, Khurram; Deswal, Anita; Jneid, Hani; Alam, Mahboob; Ballantyne, Christie M.; Petersen, Laura A.; et al.
Abstract : Background: Obesity is a growing epidemic that has been linked to the development of cardiovascular disease (CVD). Guideline-directed medications for secondary prevention and risk factor control are recommended for patients with all forms of CVD. The association of body mass index (BMI) with use of medications for secondary prevention and risk factor control in patients with CVD are poorly understood. Methods and Results: We identified 1 122 567 patients with CVD receiving care in 130 Veterans Affairs facilities from October 1, 2013, to September 30, 2014. Five groups were stratified by BMI—underweight (BMI, <18.5 kg/m 2 ), normal (BMI, 18.5–24.9 kg/m 2 ), overweight (BMI, 25–29.9 kg/m 2 ), obese (BMI, 30–39.9 kg/m 2 ), and extremely obese (BMI, ≥40 kg/m 2 ). A composite of 4 measures—blood pressure <140/90 mm Hg, hemoglobin A1c ⩽9% in diabetic patients, statin use, and antiplatelet use—termed optimal medial therapy (OMT) was compared among groups. Multivariable logistic regression was performed with normal BMI as the referent category. Underweight patients comprised 12 623 (1.1%), normal BMI 230 471 (20.5%), overweight 413 590 (36.8%), obese 404 105 (36%), and extremely obese 61 778 (5.5%) of the cohort. Only 43.7% of the entire cohort received OMT, and this was the highest in the overweight group. Adjusted odds ratios for receiving OMT were 0.81 (95% CI, 0.77–0.85), 1.11 (95% CI, 1.10–1.13), 1.08 (95% CI, 1.06–1.09), and 0.87 (95% CI, 0.85–0.89), for patients who were underweight, overweight, obese, and extremely obese, respectively, compared with normal BMI. Conclusions: OMT was low in the entire cohort. There is an inverse U-shaped relationship between OMT and BMI with patients who are underweight and extremely obese less likely to receive OMT compared with patients with normal BMI. Abstract : Supplemental Digital Content is available in the text.